DUE DILIGENCE IN BUSINESS TRANSACTIONS: LEGAL RISK ASSESSMENT IN INTERNATIONAL NEGOTIATIONS AND PARTNERSHIPS (International Seven Journal of Multidisciplinary, 2022)
In the context of globalized commerce, legal due diligence has emerged as a vital strategic instrument for mitigating risks in international business transactions and partnerships. This paper examines the multifaceted role of legal due diligence in identifying legal liabilities, ensuring regulatory compliance, and supporting decision-making processes in cross-border operations. Drawing on academic and regulatory sources, the discussion highlights key areas of legal risk, including anti-corruption compliance, intellectual property rights, and the emerging significance of environmental, social, and governance (ESG) frameworks. The complexities inherent in navigating multiple legal systems and jurisdictional standards are addressed, emphasizing the necessity of multidisciplinary approaches and technological tools for efficient risk assessment. The findings reinforce the importance of proactive legal due diligence as a foundational practice for building resilient and legally compliant international partnerships.